Chinese Cinderella The true story of an unwanted daughter - Mah, Adeline Yen (New York : Delacorte Press, 1999)
Adeline Yen Mah tells the story of her childhood as an unwanted, unloved "bad luck" child of an affluent Chinese family. Based on the memoir "Falling Leaves."
75215
Keywords: Mah, Adeline Yen -- 1937-; Chinese Americans -- Biography -- Juvenile literature. -- California; Women physicians -- Biography -- Juvenile literature. -- California; China -- Social life and customs -- Juvenile literature